Discovering mythorealism: A corpus stylistic analysis of Yan Lianke’s novels in English - Yi Zhang; Chaoyong Zhao (PLoS ONE, 2026)
This study aims to identify the stylistic features of the literary mode Yan Lianke terms as “mythorealism” in the English translations of his novels, through corpus stylistic analysis. Using a corpus of nine translated works by Yan and a reference corpus of English translations of contemporary Chinese fiction, the analysis employs Wmatrix to detect statistically overused semantic domains and LancsBox to investigate their collocational networks and usage contexts. Combining quantitative and qualitative methods, the study identifies five foregrounded semantic patterns: political discourse, spatial narrative, natural environment, color symbolism and the supernatural. The findings show that political discourse intertwines historical events with allegorical critique; spatial narrative delineates symbolic boundaries between social and psychological worlds; color symbolism, particularly the recurrent use of red, conveys culturally resonant yet ambivalent meanings; and supernatural elements extend realism into metaphysical and philosophical realms. Supported by a representative bilingual case study which illustrates the retention of core semantic structures, the study suggests that despite translator mediation, these patterns largely reflect the enduring thematic and stylistic characteristics of Yan’s fiction. These findings offer a corpus-based empirical grounding for mythorealism and present a replicable framework for bridging semantic-domain statistics and stylistic interpretation in the study of translated literature.